ONLINE SHOPPING BEHAVIOR AMONG UNIVERSITY STUDENTS: CASE STUDY OF MUST UNIVERSITY - AHMAD, MUSHTAQ (Advances in Social Sciences Research Journal, 2018)
The goal of the research is to identify and explore most commonly purchasing products online also influencing factors on the online buying behavior of the MUST university students. Functionality, privacy, trust, firm reputation and perceived value are the major influencing factors on consumer buying online behavior. Quantitative study approached has been adopted in this study and total 100 questionnaire samples have been distributed among MUST university business faculty students. The findings indicated that about 99.0% MUST students are involved in online purchasing and most computer/electronic/ mobile are the common products purchased online. The relationship and data reliability of the influencing factors are significantly reliable and has significant relationships which justify the study hypothesis. Study concluded that among the influencing factors functionality of the web vendors ranked high importunacy followed by privacy, perceived value, firm reputation and trust. The lower ranking of trust is indicating that major respondents group feels uncomfortable or unsafe while trusting on the web vendor